PENGEMBANGAN VIDEO PEMBELAJARAN PADA MATA KULIAH SENSOR DAN KONTROL ELEKTRONIKA OTOMOTIF DAPERTEMEN TEKNIK OTOMOTIF - Atikah Hana Putri Zelvanda; Rifdarmon Rifdarmon; Irma Yulia Basri; Iffarial Nanda (Ensiklopedia of Journal, 2026)
This study aims to develop instructional video media for the Automotive Electronic Sensors and Control course as a solution to the low level of student understanding in visualizing the working principles of sensors and vehicle control systems. The research employed the 4D development model (Define, Design, Develop, Disseminate), which included needs analysis, video design, expert validation, and practicality testing with students. Validation results from material and media experts show that the developed video is highly valid, with an Aiken’s V score of 0.81. Practicality testing involving 75 students produced scores ranging from 86% to 87%, indicating that the video is highly practical, easy to use, and effective in enhancing students’ understanding of automotive sensor concepts and control systems. The study concludes that the developed video is an effective instructional medium, supports student independent learning, and is feasible for use in both classroom and self-directed learning contexts.Keywords: learning videos, automotive sensors, electronic controls, educational media, 4D models